Climatic specialisation: an explanation for the range size and distribution of bryophytes on a tropical island elevational gradient - Figenschou, Laura Kristina (Department of Biological Sciences, 2020)
Are species physiologically specialised to the specific climatic conditions in their habitats and can this explain their distributions? This thesis addresses this question using a very specific system: bryophytes on the elevational gradient of Piton des Neiges, Réunion Island. Bryophytes are expected to be specialised to fairly narrow conditions of drought, temperature and insolation, which restrict their geographic range. However, little is known about the mechanisms that connect bryophytes with climatic factors. In this thesis I test the idea of ecophysiological specialisation using reciprocal transplant experiments, along with direct laboratory measurements of species' responses to desiccation and temperature. In these experiments I use species restricted to low, mid or high elevation, as well as widespread species found along most of the gradient. The transplant experiment revealed a trend of upslope survival of restricted species, with species from all sites performing best at their elevation of origin and the site above, and badly at lower elevations. Despite macroclimate being found as an important factor shaping bryophyte range size and distribution, the effect of microhabitat could not be ignored. This was especially true for the widespread species, which showed a strong effect of microhabitat placement in the transplant experiment. Desiccation tolerance was found to increase with elevation in range-restricted species, but widespread species showed little difference in their sensitivity to desiccation, regardless of elevation of origin. Range-restricted species from low elevation were more sensitive to low temperatures and had higher optimum temperatures for photosynthesis than mid- and high-elevation species. Widespread species had narrower ranges of temperature tolerances than range-restricted species, and did not differ in their response to temperature, regardless of elevation of origin. The results of these experiments corresponded well with the climatic conditions that these species habitually experience – with extremes at the gradient peripheries and intermediate conditions in between. This thesis showed that specialisation to both macro- and microclimatic conditions can be attributed as a main driver of bryophyte range size and distribution on the elevational gradient of Piton des Neiges, Réunion Island. This research adds to the body of knowledge on the physiological responses of tropical bryophytes, which is important for species' distribution modelling. Furthermore, it provides insight into the factors that shape bryophyte distribution, critical for biodiversity management under climate change scenarios.